A multilevel analysis of work–life balance practices - Koon, Vui Yee* (Wiley, 2020)
The current study uses a multilevel analysis to examine how work–life balance (WLB) practices applied at the organizational level associate with WLB practices and performance appraisal at the individual level that affects employee commitment, underpinned by the theory of supportiveness and the relational perspective. Respondents were 319 employees and 74 managers from small and medium-sized enterprises (SMEs) of various industries in Malaysia. Results indicate that the consistency of employee perception of WLB practices and performance appraisal at individual level influence employee commitment, whereas WLB practices at the organization level have a negative influence on employee commitment. The study also found differences in perception of WLB practices between managers and employees but a high level of WLB practices agreement. The current study provides a plausible explanation that the WLB practices undertaken by the organization may not be accessible or perceived by employees, thus affecting their commitment.